Analisis Pengaruh Gaya Bahasa dalam Pemasaran Digital terhadap Minat Beli Mahasiswa - Muzainah, Muzainah; Wardania, Sri Aulia; Basri, Muh. Bahly (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2022)
Digital developments have influenced various aspects of life, especially those related to the increasingly consumerist and fast-paced lifestyle and behavior of society. One aspect affected is marketing strategy, such as the use of language styles in digital marketing. This research aims to analyze the influence of language style on Makassar State University students' buying interest. With a quantitative approach, this research involved 30 randomly selected respondents. The research results show that a relaxed, unique and direct language style has a significant influence on students' buying interest. This research makes an important contribution to more effective marketing strategies in reaching young audiences.